SPECIFIC ANASTHESIOLOGICAL AND INTENSIVE CARE FOR CIVIL POPULATION IN MILITARY CONFLICTS (1ST REPORT) - A. N. Kolesnikov (Вестник анестезиологии и реаниматологии, 2017)
The  article describes the  emergency care in  massive injury during the  military conflict (230 patients, of them 220 are civilian population, of them 7 are children; 348 cases of urgent anesthesia). Special attention is paid to organizational activities. Specifics of peri-operative provisions, intensive care are defined and given special emphasis.